2011
DOI: 10.2190/pm.41.1.h
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial to Assess Effectiveness of a Spiritually-Based Intervention to Help Chronically Ill Adults

Abstract: A minimal intervention encouraging spiritual coping was inoffensive to patients, associated with increased energy, and required no additional clinician time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 33 publications
0
30
0
5
Order By: Relevance
“…These results provide a rationale for the design of psycho-spiritual intervention trials targeting religious struggle in HD patients, as such interventions might potentially alleviate psychological distress and improve HD patients' HRQoL. A few systematic investigations of spiritually-based treatment procedures for patients with chronic diseases have been recently reported with encouraging results [51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…These results provide a rationale for the design of psycho-spiritual intervention trials targeting religious struggle in HD patients, as such interventions might potentially alleviate psychological distress and improve HD patients' HRQoL. A few systematic investigations of spiritually-based treatment procedures for patients with chronic diseases have been recently reported with encouraging results [51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…At 3 weeks, the intervention group showed greater reductions in depressive symptoms, improvement in QOL, and an improved sense of interpersonal caring from their physician . McCauley et al assigned a 28‐minute video and workbook encouraging spiritual coping to 100 chronically ill patients. Energy improved in the intervention group, and while improvements in pain, mood, health perceptions, illness intrusiveness, and self‐efficacy were not statistically significant, the exercise was inoffensive to patients and required no additional clinician time.…”
Section: Spiritual Carementioning
confidence: 99%
“…Therefore, four weeks after intervention were consid-ered as the appropriate time for measurement. Similarly, McCauley et al (39) carried out a study to assess the effectiveness of a spirituality-based intervention on chronically ill patients' health and found that their intervention was effective in reducing depressive symptoms and promoting adaptation. Moreover, Zamaniyan et al (28) reported the effectiveness of spiritual group therapy in enhancing the quality of life and the psychological well-being of patients with breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The total score of BAI was reported to have a significant correlation with the total score of the Hamilton anxiety rating scale (r = 0.72), confirming its criterion validity. Moreover, the test-retest correlation coefficient and Cronbach's alpha value of the inventory were reported to be 0.83 and 0.92, respectively (38,39).…”
Section: Instrumentsmentioning
confidence: 99%